Gambaran Perilaku Pasangan Usia Subur Penyandang Disabilitas dengan Kesuburan dan Faktor Lingkungan Sosial yang Mempengaruhinya di Kabupaten dan Kota Cirebon - Herry Nurhendriyana (Universitas Malahayati Lampung, 2024)
ABSTRACT Persons with disabilities are people who have physical, mental, intellectual and/or sensory limitations for a long period of time so that they have difficulty interacting and participating with the environment. The aim of this research is to determine the description of behavior and social environmental factors in couples of childbearing age with disabilities and fertility. Qualitative research type, with Rapid Assessment Procedures research design. There were six informants in this study (five main informants and one key informant). It is known that the success of couples of childbearing age with disabilities in having offspring is influenced by the behavior of couples of childbearing age with disabilities to have their pregnancies checked by health workers (midwives or doctors) and when giving birth they are assisted by health workers (midwives or doctors). Predisposing factors, the informant has confidence in being able to get pregnant and being able to get through the pregnancy period and being able to carry out the birth process. Reinforcing factors, the informant received support from family and peers in obtaining offspring, there was a lack of specific support from health workers. The strengthening factor of support from the family is the strongest factor in the success of couples of childbearing age with disabilities in having offspring (children). Suggestion: Increase knowledge about reproductive health, pregnancy and childbirth for couples of childbearing age with disabilities in general through health education (communication, information and education). Collaboration between the Health Service, Social Service and Manpower Service agencies with the Cirebon Disability Communication Forum regarding health programs and special skills training for people with disabilities. Keywords: Childbearing Age Couples with Disabilities, Behavior, Self-Confidence, Family Support and Peer Support ABSTRAK Penyandang disabilitas adalah orang yang memiliki keterbatasan fisik, mental, intelektual dan atau sensorik dalam jangka waktu yang lama sehingga kesulitan berinteraksi dan berpartisipasi dengan lingkungan. Tujuan dari penelitian ini untuk mengetahui gambaran perilaku dan faktor lingkungan sosial pada pasangan usia subur penyandang disabilitas dengan kesuburan. Jenis penelitian kualitatif, dengan desain penelitain Rapid Assessment Procedures. Informan dalam penelitian ini sebanyak enam orang (lima orang informan utama dan satu orang informan kunci). Diketahuinya keberhasilan pasangan usia subur penyandang disabilitas dalam memperoleh keturunan, dipengaruhi oleh perilaku pasangan usia subur penyandang disabilitas untuk memeriksakan kehamilanya ke petugas kesehatan (bidan ataupun dokter) dan saat persalianan ditolong oleh petugas kesehatan (bidan ataupun dokter). Faktor predisposisi, informan mempunyai keyakinan diri mampu hamil dan mampu melewati masa kehamilanya serta mampu melakukan proses persalinan. Faktor penguat, informan mendapatkan dukungan dari keluarga dan teman sebaya dalam memperoleh keturunan, kurangnya dukungan secara khusus dari petugas kesehatan. Faktor penguat dukungan dari keluarga merupakan faktor yang terkuat dalam keberhasilan pasangan usia subur penyandang disabilitas dalam memperoleh keturunan(anak). Peningkatan pengetahuan tentang kesehatan reproduksi, kehamilan dan persalinan pasangan usia subur penyandang disabilitas secara umum melalui penyuluhan kesehatan (komunikasi, informasi dan edukasi). Kerjasama antara instansi Dinas Kesehatan, Dinas Sosial dan Dinas Tenaga Kerja dengan Forum Komunikasi Disabilitas Cirebon mengenai program kesehatan dan pelatihan keterampilan khusus penyandang disabilitas. Kata Kunci: Pasangan Usia Subur Penyandang Disabilitas, Perilaku, Keyakinan Diri, Dukungan Keluarga dan Dukungan Teman Sebaya.